(3TQM UdGI GHf eTjTs - (3YHO Gddg Hf Ydj Hf YHO GdQMef ShjOGf GdOedjLj,J (B1234 (3g` s
(3ChdgG (B:s
(3GdMeO ddg hHYO agPG JYdjb bUOJ Hg NOeg GdfHi GdTQja Ydi GdUdGg GdJi CdbJgG GdYGde Hf eTjT s
(3BNQgG (B:s
(3bhdc HG YHGO hEf UjQJ CMeO s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B20s
(3hjdjI TQM UdGI SjOi CMeO GdHOQi dfaS GdeDda YHO Gddg GdOedjLi hdcfgG eNJdWI eY UdGI GHf eTjT JUhas
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B107 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B89s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
(3GdfSNI HgG JdhjK s
Keywords: (3GdeLGejYs